The Intelligent Threat: How Artificial Intelligence Can Compromise Our Security (Belügyi Szemle, 2024)
Aim: The aim of the study is to draw attention to the dangers of using artificial intelligence.Methodology: Alongside a relevant literature review, the author illustrates the aspects of artificial intelligence jeopardising our security by providing examples and addresses the existing and evolving regulatory environment.Findings: Artificial intelligence can directly or indirectly pose a threat to our security. The risks associated with artificial intelligence, coupled with the current rapid technological advancement, make it imperative to establish appropriate and adaptive continuous regulations to ensure the increasing use of AI comes with minimal negative consequences.Value: The study explores previously overlooked features that compromise security. Its findings can contribute to understanding how artificial intelligence can endanger our security on both narrower and broader societal levels.